The Influence of Service Quality and Employee Competence on Customer Satisfaction with Customer Trust as a Mediating Variable at PT Bank Perekonomian Rakyat Tapin Sejahtera Perseroda in Tapin Regency, South Kalimantan Province - Aprilia, Natasya Noor; Kadir, Abdul; Asruni, Asruni; Muler, Ariantho (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2026)
This study examines the influence of service quality and employee competence on customer satisfaction, with customer trust serving as an intervening variable. The research is driven by the urgent need for organizations to strengthen service quality and human resource capabilities to build trust and sustain customer satisfaction in an increasingly competitive environment. Adopting a quantitative approach, data were collected through surveys administered to customers who had directly experienced the services provided. The analysis utilized the PLS-SEM technique with SmartPLS software. The outer model evaluation confirms that all indicators meet validity and reliability standards, as reflected in outer loading values above 0.70, Average Variance Extracted (AVE) exceeding 0.50, and composite reliability and Cronbach’s alpha values within required thresholds. These results indicate that the constructs employed in the study are statistically robust. The inner model evaluation further demonstrates that service quality and employee competence both have positive and significant effects on customer trust and customer satisfaction. Customer trust is also shown to positively and significantly influence customer satisfaction. Moreover, the findings reveal that customer trust acts as a mediating variable in the relationship between service quality, employee competence, and customer satisfaction. This suggests that enhancing service quality and employee competence contributes not only directly to increased customer satisfaction but also indirectly through the strengthening of customer trust. Overall, this research provides theoretical contributions to the field of service management and offers practical guidance for organizations in formulating strategies to improve service quality and employee competence in order to achieve sustainable customer satisfaction.